2016
DOI: 10.1111/ijag.12254
|View full text |Cite
|
Sign up to set email alerts
|

Fiber spinnability of glass melts

Abstract: Fiber spinnability is the ability of a glass‐forming melt to be steadily stretched and spun into defect‐free fiber filaments. However, its quantification has not been well established owing to many controlling factors such as melt fragility, melt strength, surface tension, liquidus temperature, liquidus viscosity, and crystallization. To understand and quantify the fiber spinnability of a glass melt, we consider two key aspects: fiberizing viscosity window and melt stability. The fiberizing viscosity window is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The influence of the basalt and E-glass melt viscosity, cooling rate, structural heterogeneity, and technological defects on mechanical and thermal properties were studied in detail by Yue et al [13][14][15][16]. The authors suggest the existence of non-Newtonian extensional thinning flow in a fibrous stream [12]. This can indirectly confirm the fact that many experiments have shown that the melt flow rate through nozzles for E-glass exceeds the theoretical one by several times [17,25].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The influence of the basalt and E-glass melt viscosity, cooling rate, structural heterogeneity, and technological defects on mechanical and thermal properties were studied in detail by Yue et al [13][14][15][16]. The authors suggest the existence of non-Newtonian extensional thinning flow in a fibrous stream [12]. This can indirectly confirm the fact that many experiments have shown that the melt flow rate through nozzles for E-glass exceeds the theoretical one by several times [17,25].…”
Section: Discussionmentioning
confidence: 89%
“…The second group can be conventionally attributed to the technological parameters [12]. The effect of technological parameters (winding speed, melt temperature, nozzle diameter, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A larger η L indicates a higher glass-forming ability. Hence, η L is a governing factor for glass fiberizing processes, 4 and it is important in the design of new industrial glass compositions. For example, recently a fiber spinnability index has been proposed to quantify the ability of a glass melt to be spun into fiber filament in terms of η L .…”
Section: Introductionmentioning
confidence: 99%
“…For example, recently a fiber spinnability index has been proposed to quantify the ability of a glass melt to be spun into fiber filament in terms of η L . 4 Liquidus viscosity is typically determined by direct viscosity measurements at T L . Viscosity measurements can be performed with various types of viscometers, 5 but several factors can make it difficult to apply viscometry in many cases, for example, melt volatilization, crystallization, limited sample availability.…”
Section: Introductionmentioning
confidence: 99%
“…By performing the atomic force microscope analysis on the Ca‐Mg mixed silicate glasses, Kjeldsen et al observed a direct link between the volume of plastic flow and the Vickers hardness ( H v ), suggesting that the mixed alkaline‐earth effect on H v originates primarily from the nonlinear compositional dependence of the ability of the mixed modifier glasses to resist plastic flow . The glass fiber spinnability is sensitive to variation in the Ca/Mg ratio for the aluminosilicate glasses . The “dynamic structural mismatch model” is useful in clarifying the structural origin of mixed alkaline‐earth effect regarding mechanical and rheological properties in silicate glasses .…”
Section: Introductionmentioning
confidence: 99%